New methods for studying the Tuvan song tradition - Baranmaa, Ayasmaa D.-B. (The New Research of Tuva, 2018)
Review of: Tiron, E. L. Pesni tuvintsev-todzhintsev: zhanry yr i kozhamyk v kontse XX stoletiia [Songs of the Todzhi Tuvans: the genres of yr and kozhamyk at the end of the 20th century] / ed. by G. B. Sychenko. Novosibirsk, Nauka. 248 p. ISBN 978-5-02-038791-1 The monograph is an ethnomusical study on the two main genres of Todzhi Tuvans’ folk songs – yr and kozhamyk, which are analyzed in a comparative aspect. According to the reviewer, this is the first integrated and systemic study of the song tradition of the Todzhi rayon of the Republic of Tuva. The book reveals the similarities and differences between the two genres at their levels of functioning, semantics, poetics, versification, syllabic and rhythmic intonation, tempo, gamut, harmony and functional organization. The system of intonational culture of Todzhi Tuvans receives further examination, with the lyric sphere represented by yr and kozhamyk is found to have been almost fully preserved. The author contributes to the study of the problem of the genre in Tuvan song folklore. Based on field studies, E.L. Tiron proves the functioning of two main genres in the song tradition of Todzhi Tuvans, as well as the presence of other variations, such as lullaby (өpеi yry), wedding song (kuda yry), and songs performed at the youth night parties (oitullash kozhamyk). The author significantly expands the boundaries of kozhamyk in the figurative and thematic content of the song lyrics. The author of the monograph also provides a comparative analysis of the time and pitch parameters of the organization of two genres. Of special value is the appendix to the work containing musical transcripts of songs in the yr and kozhamyk genres with lyrics transcribed in Tuvan and Russian languages. The book is intended for specialists in the field of ethnic music and folklore studies as well as for all Tuvans who are interested in traditional musical culture.